The exergames as didactic resource to the teaching of the athletics content in school physical education - Salgado, Karen Regina; Scaglia, Alcides José (Journal of Physical Education (Maringá), 2020)
Exergames are games that allow new ways of experiencing a sport discipline. They are part of the current digital culture, and for this reason can be incorporated into the classroom as a didactic resource to teaching the contents of physical education at school. Therefore, a study was carried out with an intervention composed of eight classes directed to the teaching of athletics to the students of the fourth and fifth grade of elementary school, with the objective of applying the Xbox 360 with Kinect in class, creating learning environment to reconcile the exergames with activities done on the court and to understand the games as a possible facilitator to the learning of athletics. We verified in our study that exergames can contribute to the teaching and learning process, provided that there is pedagogical mediation, establishing itself as an interesting tool to be used in school physical education.